Bentuk Penyajian Tarian Kuntau Pada Acara Pernikahan Di Desa Bajo Kecamatan Tilamuta Kabupaten Boalemo - Inarsha Mezak, Fayza; Diah Sitharesmi, Riana; Semiaji, Trubus (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2025)
This study aims to describe the presentation of the Kuntau Dance at a wedding in Bajo Village, Tilamuta District, Boalemo Regency. The background of the study is based on the fading tradition of the Kuntau dance which is only danced by three elderly dancers, even though this dance has a meaning of protection and sacred value in traditional processions. The method used is descriptive qualitative with a case study design. Data were collected through participatory observation, in-depth interviews with traditional leaders and Kuntau performers, and photo and video documentation. Data analysis was carried out inductively through data reduction, display, and verification to produce a comprehensive description. The main findings show that the presentation of the Kuntau dance involves two types of movement (step 1 and step 2), modern costume (batik shirt, cloth trousers, cap), natural makeup, linear floor patterns, and traditional musical accompaniment (drums and gongs). The performance begins with an opening greeting, walking to escort the groom's entourage, and ends three meters from the door of the bride's house. The conclusion of the research states that the Kuntau dance is a traditional performing art of the Bajo Tribe which has transformed from sacred martial arts into a cultural attraction at wedding processions and needs to be preserved through training the younger generation, documentation, and development of cultural tourism.